Potensi Limbah Ampas Teh sebagai Alternatif Material Akustik Ramah Lingkungan - Ukhti Mutia Munifatuzzahroh; Ian Yulianti; Fianti Fianti (Faculty of Science and Education, UIN Walisongo Semarang, 2021)
The research aims to determine the potential of tea waste as an environmentally friendly alternative acoustic material. The acoustic material is made by mixing tea waste powder with fox glue and water, formed, and dried. The acoustic material was made into six samples with different compositions of tea wastes, that were 20 g, 40 g, 60 g, 80 g, 100 g, and 120 g. The value of the effectiveness of noise reduction and the coefficient of sound absorption, both were obtained the most optimum in sample 6 with a composition of 120 g, that were 10.1% and 0.07497 dB. The value of both increases with the increase of the composition of the tea wastes in the acoustic material.